2021
DOI: 10.3390/ijerph18116030
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality and Its Relationship with Individual Characteristics, Personal Experiences and Mental Health during the COVID-19 Pandemic

Abstract: While the COVID-19 has dramatically altered our lifestyle and sleep practices, the links between sleep, individual characteristics, personal experiences and mental health during the pandemic require further examination. This cross-sectional, multi-methods study examined differences in language used to describe personal experiences, and mental health, based on sleep quality during the early stages of the pandemic. N = 1745 participants (mean age 42.97 ± 14.46 years) from 63 countries responded to the survey. Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 66 publications
2
33
1
6
Order By: Relevance
“…Importantly, poor sleep quality has been linked to poorer mental health, both pre-pandemic and in the recent pandemic literature. 40 , 45 In the same global study, it has been shown that individuals who scored more than eight points on the PSQI had a three-fold increased prevalence of significant anxiety, stress and depressive symptoms, even when controlling for pandemic-related factors and demographics. 40 While further longitudinal studies are needed to uncover the directionality of these associations, it would appear that addressing poor sleep during lockdowns may help to mitigate some of the adverse mental health effects.…”
Section: The Effects Of Pandemic and Lockdown On Sleep Circadian Timing And Mental Health Across The Globementioning
confidence: 97%
See 3 more Smart Citations
“…Importantly, poor sleep quality has been linked to poorer mental health, both pre-pandemic and in the recent pandemic literature. 40 , 45 In the same global study, it has been shown that individuals who scored more than eight points on the PSQI had a three-fold increased prevalence of significant anxiety, stress and depressive symptoms, even when controlling for pandemic-related factors and demographics. 40 While further longitudinal studies are needed to uncover the directionality of these associations, it would appear that addressing poor sleep during lockdowns may help to mitigate some of the adverse mental health effects.…”
Section: The Effects Of Pandemic and Lockdown On Sleep Circadian Timing And Mental Health Across The Globementioning
confidence: 97%
“…In one global survey, nearly three quarters of respondents indicated that their sleep patterns have changed as a result of lockdowns, with the majority indicating that their sleep and wake times were delayed compared to before the pandemic, and 43% of respondents indicating that their current sleep timing was more in line with their body clock. 40 Increasing flexibility in sleep-wake routines resulting from stay-at-home orders has clearly been of benefit to many in society who would have otherwise suffered with reduced sleep opportunity due to occupational and lifestyle commitments. However, for others, being afforded greater flexibility in sleep timing appears to have resulted in more irregular sleep-wake timing, which is known to have adverse effect on academic performance and health outcomes.…”
Section: The Effects Of Pandemic and Lockdown On Sleep Circadian Timing And Mental Health Across The Globementioning
confidence: 99%
See 2 more Smart Citations
“…An online questionnaire concluded that being a woman, having an income monthly between 1000 and 5000 or >5000 CNY, not exercising and having a higher education level (baccalaureate and higher) were a risk factor for sleep disorder [37]. Nearly 50% of study participants reported poor sleep quality, which was associated with a more negative emotional tone and more mentions of money or finance-related words [38]. An online survey based in Italy helped to conclude that young people and women, as well as those with doubts about possible infection with COVID-19 and greater fear of direct contact with people infected with COVID-19 were at an increased risk of developing sleep disorders.…”
Section: Previous Studiesmentioning
confidence: 97%